2020
DOI: 10.1016/j.celrep.2020.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Is Increased in the Cerebrospinal Fluid of Humans with Obesity and Induces Memory Impairment in Mice via Pro-inflammatory TNF-α

Abstract: Graphical Abstract Highlights d CSF palmitate is increased in overweight or obese humans with cognitive impairment d CSF palmitate inversely correlates with cognitive performance in overweight humans d Palmitate impairs synaptic plasticity and memory in mice d Activated microglia and TNF-a mediate palmitate-induced impairments in memory In Brief Obesity has been associated with cognitive decline. Melo et al. show that palmitate levels are increased in the CSF of overweight and obese humans. In mice, intracereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 91 publications
2
63
1
2
Order By: Relevance
“…166 They further report that increased levels of palmitate in the CSF of aged mice provoke pro-inflammatory TNF-α cytokine production and that this can lead to memory deficits. 166 Indeed, they showed that TNF-α receptor-deficient mice treated with palmitate perform better on memory tests compared with palmitate-treated wildtype controls. 166 In addition, an intracerebroventricular injection of infliximab, a TNF-α-neutralizing antibody, was also found to improve memory and ameliorate microgliosis in mice on a high-fat diet.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 97%
See 4 more Smart Citations
“…166 They further report that increased levels of palmitate in the CSF of aged mice provoke pro-inflammatory TNF-α cytokine production and that this can lead to memory deficits. 166 Indeed, they showed that TNF-α receptor-deficient mice treated with palmitate perform better on memory tests compared with palmitate-treated wildtype controls. 166 In addition, an intracerebroventricular injection of infliximab, a TNF-α-neutralizing antibody, was also found to improve memory and ameliorate microgliosis in mice on a high-fat diet.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 97%
“…161,162 In this section, we will discuss the double-edged nature of inflammation in AD. [163][164][165][166][167][168][169][170] Resting levels of pro-inflammatory cytokines are found to be higher in the blood and cerebrospinal fluid (CSF) of AD patients, suggesting a role for them in disease pathogenesis. 171 The deposition of Aβ and resultant neuronal damage provide ligands to activate microglial phagocytosis of Aβ while also promoting microglia-mediated production of pro-inflammatory cytokines.…”
Section: Inflammatory Mediation Of Admentioning
confidence: 99%
See 3 more Smart Citations